Estimating dose delivery accuracy in stereotactic body radiation therapy: A review of in-vivo measurement methods. (August 2020) - Esposito, Marco; Villaggi, Elena; Bresciani, Sara; Cilla, Savino; Falco, Maria Daniela; Garibaldi, Cristina; Russo, Serenella; Talamonti, Cinzia; Stasi, Michele; Mancosu, Pietro
Highlights: The recent progresses on in-vivo dosimetry for SBRT were reviewed. All of the on-line QA methods used for dose estimation were considered. Best solution for error-free SBRT delivery is the use of two or more QA systems. Abstract: Stereotactic body radiation therapy (SBRT) has been recognized as a standard treatment option for many anatomical sites. Sophisticated radiation therapy techniques have been developed for carrying out these treatments and new quality assurance (QA) programs are therefore required to guarantee high geometrical and dosimetric accuracy. This paper focuses on recent advances on in-vivo measurements methods (IVM) for SBRT treatment. More specifically, all of the online QA methods for estimating the effective dose delivered to patients were compared. Determining the optimal IVM for performing SBRT treatments would reduce the risk of errors that could jeopardize treatment outcome. A total of 89 papers were included. The papers were subdivided into the following topics: point dosimeters (PD), transmission detectors (TD), log file analysis (LFA), electronic portal imaging device dosimetry (EPID), dose accumulation methods (DAM). The detectability capability of the main IVM detectors/devices were evaluated. All of the systems have some limitations: PD has no spatial data, EPID has limited sensitivity towards set-up errors and intra-fraction motion in some anatomical sites, TD is insensitive towards patient related errors, LFA is not an independent measure, DAMs are not always based on measures. In order to minimize errors in SBRT dose delivery, we recommend using synergic combinations of two or more of the systems described in our review: on-line tumor position and patient information should be combined with MLC position and linac output detection accuracy. In this way the effects of SBRT dose delivery errors will be reduced.